A Strategic Approach to Quality Management of Continuing Professional Education in the Age of Disruption - Alfredo Soeiro (2013)
How do you manage CE/CPD quality in this age of disruption? What do you do? Do you have a process? Who do you reach out to? With whom do you compare your organization? What data do you look at? What tools do you use? How do you know where you need to improve?